2023
DOI: 10.1021/acssuschemeng.2c07213
|View full text |Cite
|
Sign up to set email alerts
|

POLITAG-M-F as Heterogeneous Organocatalyst for the Waste-Minimized Synthesis of β-Azido Carbonyl Compounds in Batch and under Flow Conditions

Abstract: We herein report a waste minimization protocol for the β-azidation of α,β-unsaturated carbonyl compounds using TMSN3. The selection of the appropriate catalyst (POLITAG-M-F), in combination with the reaction medium, resulted in enhanced catalytic efficiency and a low environmental footprint. The thermal and mechanical stability of the polymeric support allowed us to recover the POLITAG-M-F catalyst for up to 10 consecutive runs. The CH3CN:H2O azeotrope has a 2-fold positive effect on the process, increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…32 Once the pine needle lignocellulosic component was isolated, the PiNe support was prepared following a chemical car-bonization method under mild conditions. 33 The as-prepared biochar was used without any further modification to immobilize Pd nanoparticles using a polyol method. 23 After the addition of H 2 PdCl 4 precursor to the diethylene glycol suspension of PiNe, the reduction step was performed at 130 °C under an Ar atmosphere, affording the final Pd/PiNe heterogeneous catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…32 Once the pine needle lignocellulosic component was isolated, the PiNe support was prepared following a chemical car-bonization method under mild conditions. 33 The as-prepared biochar was used without any further modification to immobilize Pd nanoparticles using a polyol method. 23 After the addition of H 2 PdCl 4 precursor to the diethylene glycol suspension of PiNe, the reduction step was performed at 130 °C under an Ar atmosphere, affording the final Pd/PiNe heterogeneous catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our research group (Green S.O.C. )'s commitment to developing waste-minimized protocols (Campana et al, 2020b;Valentini et al, 2023), herein is reported the synthesis of various levulinates (3a: pentyl levulinate, 3b: ethyl levulinate, 3c: butyl levulinate, 3d: octyl levulinate, 3e: isoamyl levulinate, 3f: isobutyl levulinate, 3g: isopropyl levulinate, 3h: secbutyl levulinate, 3i: cyclohexyl levulinate, 3j: tetrahydrofurfuryl levulinate, 3k: benzyl levulinate, and 3l: 5-hexenyl levulinate) by reacting LA with both primary and secondary alcohols (2a: 1-pentanol, 2b: ethanol, 2c: butanol, 2d: octanol, 2e: isoamyl alcohol, 2f: isobutyl alcohol, 2g: isopropanol, 2h: secbutyl alcohol, 2i: cyclohexanol, 2j: tetrahydrofurfuryl alcohol, 2k: benzyl alcohol, 2l: 5-hexen-1-ol, 2m: Geraniol and 2n: furfuryl alcohol), employing the developed PiNe-SO3H catalyst. This heterogeneous catalyst resulting from the valorization of pine needles urban waste, prepared through a one-pot chemical carbonization and functionalization process, demonstrated excellent stability over 10 consecutive cycles.…”
Section: A®-21mentioning
confidence: 99%